Earnings Functions, Specific Human Capital, and Job Matching: Tenure Bias Is Negative - Stevens, Margaret (Journal of Labor Economics, 2003)
This article investigates the hypothesis that when measures of specific human capital (such as job tenure) are included in earnings functions, there may be a sample selection bias because of job‐matching effects—because workers with high unobserved match quality receive and accept high wage offers. We develop a model for wage offers in a labor market characterized by both specific human capital and job matching. The model provides a theoretical basis for empirical earnings functions containing specific capital, and it demonstrates that sample selection bias reduces the estimated return to specific human capital and tenure.